Anthropogenic Intensity-Determined Assembly and Network Stability of Bacterioplankton Communities in the Le’an River - Wu, Bobo; Wang, Peng; Devlin, Adam Thomas; She, Yuanyang; Zhao, Jun; Xia, Yang; Huang, Yi; Chen, Lu; Zhang, Hua; Nie, Minghua; Ding, Mingjun (Frontiers in Microbiology, 2022)
Bacterioplankton are essential components of riverine ecosystems. However, the mechanisms (deterministic or stochastic processes) and co-occurrence networks by which these communities respond to anthropogenic disturbances are not well understood. In this study, we used high-throughput sequencing of Illumina HiSeq, integrated niche-neutrality dynamic balancing and co-occurrence network analysis to investigate the dispersal dynamics of microbial communities under different human activity intensity along a subtropical river. The results showed that the lower reaches (high human activity intensity) increased bacterioplankton community composition change and led to a significant increase of plankton diversity. Human activity intensity changes influenced bacterioplankton community assembly primarily by regulating the deterministic-stochastic balance, with deterministic processes becoming more important with increased human activity intensity. Bacterioplankton molecular ecological network stability and robustness was higher on average in the upper reaches (where there is lower human activity intensity), but a human activity intensity increase of about 10%/10% will reduce co-occurrence network stability of bacterioplankton community by an average of 0.62%/0.42% in the dry and wet season, respectively. Proteobacteria, Bacteroidetes and Actinobacteria were the dominant phyla (with high abundances) in bacterial networks and were not altered by spatial and temporal distribution. In addition, water chemistry (especially NO3--N and Cl- ) contributed more to explaining community assembly (especially the composition) than geographic distance and land use in the dry season, while the bacterioplankton community (especially the bacterioplankton network) was more influenced by geographic distance (especially river length and mean dendritic stream length) and land use (especially forest regions) in the wet season. Our research provides a new perspective of community assembly in rivers and important insights into future research on environmental monitoring and classified management of aquatic ecosystems under the influence of human activity.